An ultra-long life aqueous full K-ion battery. Issue 5 (12th January 2021) - Li, Yibo; Deng, Wenjun; Zhou, Zhuqing; Li, Chang; Zhang, Man; Yuan, Xinran; Hu, Jun; Chen, Haibiao; Li, Rui
Abstract : A high voltage aqueous full K-ion battery exhibits an ultra-long lifespan of 30 000 cycles and a high energy density of 47.3 W h kg −1 . Abstract : Aqueous full K-ion batteries (AFKIBs) featuring high safety, low cost, and environmental friendliness represent the future of advanced energy storage technologies. However, current AFKIB systems are still in need of suitable electrolytes and electrode materials, not to mention durability. Here, we report a "rocking-chair" type aqueous full K-ion system with KTi2 (PO4 )3 /C crystalline nanoparticles as the anode material with near zero-strain, iron hexacyanoferrate as the cathode, and 21 m KCF3 SO3 as a water-in-salt electrolyte. Benefitting from the fast reaction kinetics and high structural stability of KTi2 (PO4 )3 /C, the full battery achieves a high capacity retention of 96.7% over 30 000 cycles, excellent rate performance with full charge and discharge in 1 minute, and a high energy density of 47.3 W h kg −1 . Demonstration of the performance of this AFKIB system expands the avenues of exploration for large-scale energy storage.